World’s women 2015–2016: Transforming economies, realizing rights - UN Women (New York UN Women)
"Progress of the World’s Women 2015–2016” brings together human rights and economic policymaking, and provides the key elements for a far-reaching new policy agenda that can transform economies and make women’s rights a reality. Through solid in-depth analysis and data, this evidence-based report provides key recommendations on moving towards an economy that truly works for women, for the benefit of all. (UN Women)
​Executive summary: making progress/stories of change making women’s rights real: transforming women’s lives in north-eastern brazil 1. Substantive equality for women: the challenge for public policy 2. Transforming work for women’s rights  3. Making social policy work for women  4.towards an enabling macroeconomic environment
UN Women’s flagship report
Includes bibliographical refences (p.315-337)
Keywords: Labour market; WOMEN WORKERS; EQUALITY; Empowerment; Gender Equality; Violence against women